2022
DOI: 10.3390/ijms232113197
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Decorated, Amine Functionalized Ni-, Cd- and Co-Ferrite Nanospheres as Novel and Effective Catalysts for 2,4-Dinitrotoluene Hydrogenation

Abstract: 2,4-diaminotoluene (TDA) is one of the most important polyurethane precursors produced in large quantities by the hydrogenation of 2,4-dinitrotoluene using catalysts. Any improvement during the catalysis reaction is therefore of significant importance. Separation of the catalysts by filtration is cumbersome and causes catalyst loss. To solve this problem, we have developed magnetizable, amine functionalized ferrite supported palladium catalysts. Cobalt ferrite (CoFe2O4-NH2), nickel ferrite (NiFe2O4-NH2), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The developed Pd/CoFe 2 O 4 bentonite-based catalyst was compared to 14 other systems 11 , 12 , 12 , 13 , 36 applied in DNT hydrogenation by using the MIRA21 model 14 . It was found that the bentonite-based catalyst has a MIRA21 number of 11.09, which is just slightly lower than the best (11.50) and ranks as 8th within the list of 15 catalysts (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…The developed Pd/CoFe 2 O 4 bentonite-based catalyst was compared to 14 other systems 11 , 12 , 12 , 13 , 36 applied in DNT hydrogenation by using the MIRA21 model 14 . It was found that the bentonite-based catalyst has a MIRA21 number of 11.09, which is just slightly lower than the best (11.50) and ranks as 8th within the list of 15 catalysts (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, a catalyst library was created regarding the 2,4-dinitrotoluene catalytic hydrogenation reaction based on the MIRA21 model [20]. This database contains 58 catalysts and the corresponding multiparametric characterization (see Supplementary Information) [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. All in all, five types of descriptors were considered (Table 1).…”
Section: Catalyst Librarymentioning
confidence: 99%
“…Nanomaterials are continuously increasing in popularity for their advantageous properties in catalysis [ 1 ], carbon dioxide sequestration [ 2 , 3 , 4 ] and biological applications [ 5 ]. Among the various nanomaterials, magnetic nanoparticles (MNPs) are used for biological applications, such as magnetic resonance imaging [ 6 ], hyperthermia treatment [ 7 ], drug delivery [ 8 ] or the isolation of macromolecules [ 9 ], like deoxyribonucleic acid (DNA).…”
Section: Introductionmentioning
confidence: 99%